Avaliação da influência da substituição do graute pela argamassa de assentamento no preenchimento de prismas de blocos de concreto submetidos à compressão axial - Schumacher, Taiur (2022)
This research sought to statistically analyze whether it is mechanically feasible to replace the use of grout with the same mortar to fill the septa of concrete blocks in tests of prisms subjected to simple axial compression. Two types of prisms were tested, with concrete blocks and one-resistance grout and three-resistance mortar, totaling 108 prisms, this replacement is necessary to avoid bottlenecks during the masonry construction stage, as grout is often produced on site. generating setbacks, thus, it will be possible to add more agility to the work without structurally harming the building. In conclusion, through the analysis of results, it was found that according to the statistical analysis of Student's t, there is no significant difference between the compressive strengths of the prisms that used the 8 MPa settlement and filling mortar and the prisms that used the 10 MPa grout and the 6 MPa laying mortar, in the other prism series there was a significant difference. In addition, regarding the failure mode, it was observed that for prisms mortared with mortar from 6 MPa, there is a similarity with the failure form of grouted prisms.